A Non-cooperative Foundation of Core-Stability in Positive Externality NTU-Coalition Games - Michael Finus; Bianca Rundshagen (Fondazione Eni Enrico Mattei (FEEM), 2003)
We identify the core as an appealing stability concept of cooperative game theory, but argue that the non-cooperative approach has conceptual advantages in the context of economic problems with externalities. Therefore, we derive a non-cooperative foundation of core-stability for positive externality NTU-games. First, in the spirit of Hart/Kurz (1983), we develop a game that we call ?-game and show that strong Nash equilibria coalition structures in this game are identical to ?- and ?-core stable coalition structures. Second, as a by-product of the definition of the ?-game, we develop an extension called an ?-game. Finally, we compare equilibria in the ?- and ?-game with those in the ?- and ?-game of Hart and Kurz (1983).
Keywords: C72; 330; Core-stability; non-cooperative game theory; positive externality games; Transferierbarer Nutzen; Core; Koalition; Externer Effekt; Theorie; Nichtkooperatives Spiel